Acquired cervical spinal arachnoid diverticulum in a cat. (5th December 2014) - Adams, R. J.; Garosi, L.; Matiasek, K.; Lowrie, M.
Abstract : A one‐year‐old, female entire, domestic, shorthair cat presented with acute onset non‐ambulatory tetraparesis. Magnetic resonance imaging was consistent with a C3‐C4 acute non‐compressive nucleus pulposus extrusion and the cat was treated conservatively. The cat was able to walk after 10 days and was normal 2 months after presentation. The cat was referred five and a half years later for investigation of an insidious onset 3‐month history of ataxia and tetraparesis. Magnetic resonance imaging of the cervical spine was repeated, demonstrating a spinal arachnoid diverticulum at C3 causing marked focal compression of the spinal cord. This was treated surgically with hemilaminectomy and durectomy. The cat improved uneventfully and was discharged 12 days later.